Новые данные о долгоносиках рода Tychius (Coleoptera, Curculionidae) - Карасев, В.П. (Вестник зоологии, 1993)
Four new species of the genus Tychius Germ, are described: T. robertoi sp. n. (type-locality: Uzbekistan, West Tien-Shan, Chimgan, h—1500 m, on Astragalus anisomerus); T. sogdianus (type-Ioca-lity: Tadjikistan, Sanglok ridge, Sebiston, h — 1200 m, on Astragalus anisomerus); T. goliathus (type-locality: Turkmenistan, West Kopetdag, Kara-Kala); T. scythicus sp. n. (Volgograd region, Tinguta, on Astragalus sp.). By the examination of the species a synonymy of Miccotrogus taukumicus Bajt= and Tychius alhagi Faust, syn. n. has ben revealed.